2020
DOI: 10.20473/fmi.v56i3.22165
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Pre PRP Injection and Post Elevation Flap at Extended Random Flap Rat Skin

Abstract: Closure of the defect with a random skin flap is constrained by the extent of the defect area. Several studies have shown the benefits of administration of PRP (Platelet Rich Plasma) in random skin flap. The purpose of this study is to compare the effect of PRP injection given before flap elevation, after flap elevation and control on the extended random skin flap procedures in rats. This was an experimental study with randomized posttest-only control group design (n=27, divided into 3 treatment groups) that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…25 In a recent study, Nugroho et al demonstrated that local administration of PRP injection 24 hours prior to random skin flap elevation procedure increased flap viability in Wistar rats. 10 Our findings align with this previous research, indicating that flap preconditioning with subcutaneous injection of PRP 1 day prior to flap procedure increased flap survival by 20.1% compared with those without PRP, even under diabetic conditions. Previous research by Qian et al has also confirmed the effects of PRP in augmenting collagen production and promoting tissue regeneration in diabetic rats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…25 In a recent study, Nugroho et al demonstrated that local administration of PRP injection 24 hours prior to random skin flap elevation procedure increased flap viability in Wistar rats. 10 Our findings align with this previous research, indicating that flap preconditioning with subcutaneous injection of PRP 1 day prior to flap procedure increased flap survival by 20.1% compared with those without PRP, even under diabetic conditions. Previous research by Qian et al has also confirmed the effects of PRP in augmenting collagen production and promoting tissue regeneration in diabetic rats.…”
Section: Discussionsupporting
confidence: 92%
“…Similar phenomenon have been observed in previous studies utilizing PRP to aid in skin defect closure. (10,11) Immediately after random skin flap elevation, perfusion pressure of the flap decreases, which then increases the risk of distal flap necrosis. Ischemia-reperfusion injury exacerbates the insult to flap survival due to elevated reactive oxygen species and the inflammatory cascade, leading to vasoconstriction, platelet aggregation, and vessel occlusion(12).…”
Section: Discussionmentioning
confidence: 99%